Internal company determinants of sustainable growth rate: empirical investigation on an emerging market - Naumoski, Aleksandar (My University, 2022)
The growth of companies is always an important topic both among corporate managers and among researchers. Company’s growth requires undertaking investment projects that will increase the production capacity of the company and the possibility of generating revenue. But, the way of financing the growth, ie. of capital investment, is crucial for the survival of the company. The growth of the company can be understood by the saying "it takes money to generate more money". The most important source of financing for new capital investments are the company's own sources that provide financial stability in the long run. But if the company is not able or does not want to issue new shares, then its own sources are reduced only to retained earnings. In conditions of targeted capital structure, as a ratio between debt and equity, retained earnings is a limiting factor for the growth of the company. If the company does not want to change the capital structure, then the additional borrowing is proportional to the growth of retained earnings. Hence, the retained earnings rate is the only rate at which a company can grow. That is the rate of sustainable growth. It is the only rate of growth of sales revenue, which will not put pressure on the company's financial resources. This paper aims to investigate the inter-company determinants of the sustainable growth rate in the case of companies in the Republic of Northern Macedonia. Using accounting data on a sample of companies listed on the Macedonian Stock Exchange for the period 2010 - 2020, we conducted a regression analysis panel. We found that the company's sustainable growth rate is positively related to profit margin, retention ratio, asset turnover, financial leverage, and ROE. The sustainable growth rate of Macedonian companies has a negative relationship with operating cash flow, company size, growth opportunities, and non-debt tax shield.
Keywords: sustainable growth rate, retention ratio, North Macedonia